China's CO2 emissions from power generating stations: A first exploration - Limin Du; Aoife Hanley; Katrin Rehdanz (Kiel Institute for the World Economy (IfW), 2014)
Our analysis is the first of its kind to explore patterns of subsidization and CO2 emissions in China's electricity producing sector. Applying data for all power plants across China and controlling for the age, capacity and location of generating stations, we find that plants attracting a higher government subsidy are also worryingly the plants generating a disproportionate share of CO2 emissions. This distortion is incongruent with China's aspiration for a greener economy but may be eliminated if China delivers on its November 2013 announcement to review many industry subsidies on its way to a fully-fledged market economy (Bloomberg News, 28.02.2014).
Keywords: Q53; Q48; 330; CO2 emissions; China; energy sector; plant-level data